2002
DOI: 10.1152/ajpendo.00517.2001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of protein synthesis by both insulin and amino acids is unique to skeletal muscle in neonatal pigs

Abstract: In neonatal pigs, the feeding-induced stimulation of protein synthesis in skeletal muscle, but not liver, can be reproduced by insulin infusion when essential amino acids and glucose are maintained at fasting levels. In the present study, 7- and 26-day-old pigs were studied during 1) fasting, 2) hyperinsulinemic-euglycemic-euaminoacidemic clamps, 3) euinsulinemic-euglycemic-hyperaminoacidemic clamps, and 4) hyperinsulinemic-euglycemic-hyperaminoacidemic clamps. Amino acids were clamped using a new amino acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
217
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(237 citation statements)
references
References 61 publications
15
217
4
Order By: Relevance
“…This feeding-induced activation of the IR, IRS-I, PI 3-kinase, and protein kinase B decreases with development in parallel with the developmental decline in the feeding-induced activation of translation initiation factors that regulate the binding of mRNA to 43S ribosomal complex. These developmental changes also parallel the developmental changes in the ability of feeding and insulin infusion to stimulate protein synthesis and are specific to skeletal muscle (13,15). Because of the profound developmental decline in an initial step in the insulin-signaling cascade, i.e., the tyrosine phosphorylation of the IR (37), it was crucial that we ascertain the mechanism involved in this developmental decline in IR activation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This feeding-induced activation of the IR, IRS-I, PI 3-kinase, and protein kinase B decreases with development in parallel with the developmental decline in the feeding-induced activation of translation initiation factors that regulate the binding of mRNA to 43S ribosomal complex. These developmental changes also parallel the developmental changes in the ability of feeding and insulin infusion to stimulate protein synthesis and are specific to skeletal muscle (13,15). Because of the profound developmental decline in an initial step in the insulin-signaling cascade, i.e., the tyrosine phosphorylation of the IR (37), it was crucial that we ascertain the mechanism involved in this developmental decline in IR activation.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we also studied the mechanisms involved in PTP1B activation by measuring the association of PTP1B with the IR, the tyrosine phosphorylation of PTP1B, and the association of PTP1B with Grb2 adaptor protein. For comparison, similar measurements were also made in liver, an organ in which insulin does not stimulate protein synthesis (14,15) and which shows no developmental decline in insulin signaling (37).…”
mentioning
confidence: 99%
“…Similarly, Davis et al (2002) have observed a developmental decline in amino acid-induced stimulation of hepatic protein synthesis in the growing animal. From these studies, one might infer that there is a decreased sensitivity of the liver to amino acids during ageing.…”
Section: Towards a Portal Amino Acid Signal?mentioning
confidence: 85%
“…Previously, our group has developed and successfully implemented a stable isotope method to measure the in vivo fractional synthesis and breakdown rates (FSR 2 and FBR, respectively) of skin protein (1)(2)(3). Using this and other methods, we and others have reported the unique features of skin and wound protein metabolism (1,2,4) and its responses to nutritional and hormonal interventions (3,5,6). Amino acid (AA) supplementations and insulin (INS) are of particular interest among these interventional factors due to their well known anabolic effect on muscle and importance in wound healing (7,8).…”
mentioning
confidence: 99%
“…The skin protein NB did not change in response to any treatment as compared with the control group (3). In 7-day-old neonatal pigs, both INS alone and INS ϩ AA increased the skin protein FSR, whereas in 26-day-old pigs only INS ϩ AA increased the skin protein FSR (5). The effect of AA and INS has been also studied in an animal model of skin wounds (9) and donor site wounds in burn patients (10).…”
mentioning
confidence: 99%